Impact of online health education on attention-deficit/hyperactivity disorder screening results and parenting stress among school-aged children - Tan, Jing; Yi, Wenxia; Shen, Jianna; Peng, Bin; Gong, Min; Li, Feng; Chen, Li (Frontiers in Psychiatry, 2025)
AimsTo investigate the effects of an online health education lecture on the positive screening rate of attention-deficit/hyperactivity disorder (ADHD) and parenting stress among parents of children diagnosed with or screened positive for ADHD.MethodsUsing stratified proportional random cluster sampling, 14 primary schools in Chongqing were selected to conduct an online lecture about ADHD for parents and teachers. A total of 2,611 questionnaires were collected (1,508 intervention group, 1,103 control group).ResultsThe lecture did not significantly affect the positive screening rate of ADHD (parents: β=-0.37, p=0.208; teachers: β=0.53, p=0.338); however, the positive screening rate increased post-intervention. Inattention scores were higher in the intervention group (β=0.42, p=0.040). Parents as primary caregivers were associated with lower ADHD symptom scores (β=-0.61, p=0.022). Lower parental education levels were associated with higher ADHD screening rates (β=0.49, p=0.039) and symptom scores (β=0.60, p=0.022). Teachers with 10-19 years of experience had higher positive screening rates (β=1.26, p=0.005) and symptom scores (β=2.60, p<0.001). The intervention did not affect parenting stress (Z=-1.413, p=0.158).ConclusionsThe lecture’s effects were relatively weak, using questionnaires may have facilitated health communication. Individual characteristics of parents and teachers should be considered in assessments (ClinicalTrial.gov ID: NCT05231902).